Composition

By using a composition with latent heat characteristics, the composition cures at room temperature, the problem of difficult heat generated by the heating element in the battery module or battery pack is solved, and uniform heat control and prevention of abnormal conditions are achieved.

CN119604570APending Publication Date: 2025-03-11LG CHEM LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055697.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2023-08-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In existing battery modules or battery packs, the heat generated by the heating element can easily cause chain ignition or explosion, and it is difficult to effectively control the heat.

Method used

A curable composition is used that cures at room temperature and has latent heat characteristics, which can evenly maintain product temperature and reduce the impact on other components in the event of abnormal heating or explosion.

Benefits of technology

The composition can effectively control the heat inside the battery module or battery pack, prevent chain ignition or explosion, and maintain stable performance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604570A_ABST
    Figure CN119604570A_ABST
Patent Text Reader

Abstract

The invention relates to a composition and application thereof. The composition of the present application can be applied to a product that generates heat during driving or maintenance, thereby serving as a material capable of handling heat. The composition of the present application can be applied to a product in which a plurality of heating elements are integrated, thereby effectively treating heat generated by the elements while uniformly maintaining the temperature of the product. Furthermore, the composition of the present application is applied to the product, whereby even if abnormal heat, explosion or fire occurs in any one of the plurality of elements, it is possible to prevent or minimize the influence of such heat, explosion or fire on other adjacent elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0108817, dated August 30, 2022, and Korean Patent Application No. 10-2023-0113206, dated August 28, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0002] The present application relates to a composition, a cured body, a method for preparing the composition, and a battery module. Background Art

[0003] Batteries can be roughly divided into primary batteries and secondary batteries. Secondary batteries are also called rechargeable batteries, which can be charged and used repeatedly. Secondary batteries can be exemplified by nickel-cadmium batteries, nickel-metal hydride batteries, nickel-hydrogen batteries, or lithium secondary batteries.

[0004] Secondary batteries have emerged as a major energy storage technology and are applied or studied for use in various fields including home appliances, industry, transportation, and power storage fields, and the like.

[0005] Depending on the purpose, a so-called battery module may be constructed using a plurality of battery cells, or a so-called battery pack may be constructed using a plurality of battery modules.

[0006] For example, when secondary batteries are used as a power source for so-called electric vehicles such as electric propulsion vehicles, hybrid electric vehicles (HEV), battery electric vehicles (BEV), or plug-in hybrid electric vehicles (PHEV), a plurality of unit battery cells are used to construct a battery module or battery pack to meet the required power and capacity requirements.

[0007] In a battery module or battery pack, a plurality of unit battery cells are positioned adjacent to each other. Therefore, heat or flame generated from any one or some battery cells inside the battery module or battery pack may easily affect other adjacent battery cells and, in some cases, may cause chain fire or explosion, etc. Summary of the invention

[0008] Technical issues

[0009] The present application relates to compositions and uses thereof. The compositions of the present application can be applied to products that generate heat during driving or maintenance, thereby being used as materials that can handle heat. The compositions of the present application can be applied to products in which a plurality of heating elements are integrated, thereby effectively handling the heat generated by the elements while uniformly maintaining the temperature of the product. In addition, the compositions of the present application are applied to products, so that even if abnormal heating, explosion or fire occurs in any one of the plurality of elements, the influence of such heating, explosion or fire on other adjacent elements can be prevented or the influence of such heating, explosion or fire on other adjacent elements can be minimized. The compositions of the present application can also perform the above functions stably for a long time.

[0010] The present application may also provide a cured product formed from the composition, or uses of the composition or the cured product.

[0011] Technical Solution

[0012] Among the physical properties mentioned in this specification, unless otherwise specified, physical properties affected by temperature are physical properties measured at room temperature.

[0013] In the present specification, the term room temperature is a natural temperature without heating or cooling, which means, for example, any temperature in the range of about 10° C. to 30° C., for example, a temperature around 23° C. or 25° C. In addition, unless otherwise specified in the present specification, the unit of temperature is ° C.

[0014] Among the physical properties mentioned in this specification, unless otherwise specified, the physical properties affected by pressure are physical properties measured under normal pressure. The term normal pressure refers to the natural pressure without pressurization or decompression, which generally refers to about 1 atmosphere (about 700 mmHg to 800 mmHg) as normal pressure.

[0015] Among the physical properties mentioned in this specification, unless otherwise specified, the physical properties affected by humidity are physical properties measured under standard humidity. In this specification, standard humidity means humidity around 40% or 50% as relative humidity.

[0016] In this specification, the term heat generating product means a product that generates heat during operation or storage process, or includes a heat generating member (heat generating element), and such heat must be controlled for reasons such as product performance and / or stability.

[0017] The present application relates to compositions. In this specification, the term composition means a mixture of two or more components, or a composition comprising chemical reactants or physical reactants of two or more components.

[0018] The composition may be a composition that can be cured, ie, a curable composition. In the present specification, the term curing is a phenomenon in which the hardness and / or viscosity of the composition increases due to a physical reaction and / or a chemical reaction, or an interaction.

[0019] The composition may be of an energy beam curing type, a moisture curing type, a heat curing type, or a room temperature curing type, or a hybrid curing type in which two or more of the above curing methods are applied.

[0020] In an energy beam curing composition, the composition can be cured by irradiating it with an energy beam such as ultraviolet light; in a moisture curing composition, the composition can be cured by keeping the composition under a suitable humidity; in a heat curing composition, the composition can be cured by applying a suitable heat to the composition; and in a room temperature curing composition, the composition can be cured by keeping the composition at room temperature. In a mixed curing composition, the composition can be cured by applying two or more of the above methods at the same time, or by applying them in stages. In one example, the composition of the present application can be a room temperature curing composition. For example, the composition of the present application can be cured while being kept at room temperature without separate energy beam irradiation and moisture application, etc.

[0021] The composition of the present application can be a one-component composition or a two-component composition. A one-component composition is a composition in which the components required for curing are stored in a mixed state, while a two-component composition is a composition in which the components required for curing are stored in a physically separated state. A two-component composition generally comprises a so-called main agent part and a curing agent part, and in order to cure, the main agent part and the curing agent part are mixed. When the composition of the present application is a two-component composition, the composition can be a main agent part or a curing agent part of the two-component composition, or a mixture of a main agent part and a curing agent part.

[0022] Composition can form the solidified body that shows latent heat in the predetermined temperature range.Latent heat is usually defined as the heat required for the change of state (phase transition) of the material.However, in this specification, when the solidified body shows latent heat, it is not always necessary to cause the overall change of state.The latent heat of the solidified body in the present application can appear in the change of state process of the component included in at least a part of the solidified body or the solidified body.

[0023] In the present application, the situation that solidified body shows latent heat means that in the DSC (Differential Scanning Calorimeter, differential scanning calorimeter) analysis carried out in the manner described in the "1. Latent Heat Measurement" part in the embodiments of this specification, the solidified material shows an endothermic peak. In an example, the process in which the solidified body shows latent heat can be basically an isothermal process. Therefore, the solidified body can be applied to heat-generating products to control heat while uniformly maintaining the temperature of the product. In addition, the solidified body can minimize the influence of abnormal heating, explosion and / or ignition occurring in a product on other adjacent products, or prevent the influence of abnormal heating, explosion and / or ignition occurring in a product on other adjacent products.

[0024] The lower limit of the latent heat exhibited by the solidified body may be, for example, about 20 J / g, 22 J / g, 24 J / g, 26 J / g, 28 J / g, 30 J / g, or 32 J / g, and the upper limit thereof may also be about 50 J / g, 48 J / g, 46 J / g, 44 J / g, 42 J / g, 40 J / g, 38 J / g, 36 J / g, 34 J / g, 32 J / g, 30 J / g, or 28 J / g. The latent heat may be in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.

[0025] In one example, the temperature zone in which the solidified body exhibits latent heat (hereinafter, may be referred to as the latent heat zone) may be adjusted. In the present specification, the term latent heat zone is a zone between the starting temperature of the latent heat zone determined in the DSC analysis measured in the manner described in the "1. Latent Heat Measurement" section of the embodiments of the present specification and the ending temperature of the latent heat zone. The temperature at the inflection point of the endothermic peak at the left starting point of the endothermic peak determined in the DSC analysis may be designated as the latent heat zone starting temperature, and the temperature at the inflection point of the endothermic peak at the right starting point may be designated as the latent heat zone ending temperature. In the DSC analysis, one or two or more endothermic peaks may be determined, and even when two or more endothermic peaks are determined, the temperature of the inflection point of the endothermic peak at the point where the first endothermic peak starts (starting from the left) may be designated as the latent heat zone starting temperature, and the temperature of the inflection point of the endothermic peak at the point where the last endothermic peak ends (starting from the right) may be designated as the latent heat zone ending temperature.

[0026] The lower limit of the latent heat zone starting temperature of the solidified body disclosed in the present specification may be about 20° C., 24° C., 26° C., 27° C., 28° C., 30° C., 32° C., 34° C., 36° C., 38° C., or 40° C., and the upper limit thereof may be about 60° C., 58° C., 56° C., 54° C., 52° C., 50° C., 48° C., 46° C., 44° C., 42° C., 41° C., or 40° C. The latent heat zone starting temperature may be in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0027] The lower limit of the latent heat zone end temperature of the solidified body disclosed in the present specification may be about 30° C., 32° C., 34° C., 36° C., 38° C., 40° C., 42° C., 44° C., 46° C., or 48° C., and the upper limit thereof may be about 100° C., 95° C., 90° C., 85° C., 80° C., 75° C., 70° C., 65° C., 60° C., 55° C., 50° C., or 48° C. The latent heat zone end temperature may be in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0028] The width of the latent heat zone of the solidified body may be within a specific range. The width of the latent heat zone is a value obtained by subtracting the latent heat zone starting temperature from the latent heat zone end temperature. The lower limit of the width of the latent heat zone may be about 1°C, 3°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 15°C, 20°C, 25°C, 30°C, or 35°C, and the upper limit thereof may be about 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, or 10°C. The width of the latent heat zone may be within a range greater than or equal to, or greater than any one of the above lower limits; or within a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.

[0029] The solidified body exhibiting latent heat characteristics is applied to various heat-generating products so that the related products can operate within a stable and uniform temperature range. In addition, the solidified body is applied to products including a plurality of heat-generating elements arranged relatively adjacent to each other so that the overall temperature of the product can be uniformly maintained. In addition, the solidified body can minimize the influence of abnormal heating, fire and / or explosion occurring in one element of the product on other elements or prevent the influence of abnormal heating, fire and / or explosion occurring in one element of the product on other elements. In particular, the solidified body exhibiting latent heat characteristics can be applied to products whose driving temperature must be maintained within the range of about 15°C to 60°C (for example, secondary battery cells, or battery modules or battery packs including a plurality of battery cells) to effectively control heat.

[0030] The solidified body can stably maintain latent heat characteristics for a long time. In addition, even when the solidified body is exposed to repeated heating and cooling cycles, the latent heat characteristics of the solidified body can also be maintained. In order to make the solidified body show latent heat characteristics, the composition can include a so-called phase change material (PCM) (hereinafter, may be referred to as PCM). As PCM, a material that absorbs heat while undergoing a phase transition from solid to liquid can be used. Once such a PCM is exposed to heat, it can be converted into a liquid phase, and therefore lost from the solidified body. Therefore, in this case, if the solidified body shows a latent heat once, and then is exposed to heat again, the latent heat may be reduced or disappear, and if it is exposed to repeated heating and cooling, the latent heat characteristics may eventually be lost. In the present application, even after the PCM is converted into a liquid phase, by selecting a curable resin component forming a solidified body, adjusting the degree of crosslinking, adjusting the type and ratio of the PCM and / or adjusting the method for preparing the composition, it will not be lost in the solidified body, and can be maintained. Therefore, the latent heat characteristics of the solidified body can be stably maintained for a long time, and even when the solidified body is exposed to repeated heating and cooling, the latent heat characteristics can also be maintained. In particular, the above effects can be maximized by applying a characteristic filler to be described below.

[0031] For example, under the condition of holding at 80° C. for 24 hours, the cured body may show a weight change rate less than or equal to, or less than a certain level. The weight change rate (ΔW) is evaluated according to the following equation 1, which is determined by the method in “9. Leakage evaluation” of the Examples section.

[0032] [Equation 1]

[0033] ΔW=100×(Wf-–Wi) / Wi

[0034] In Equation 1, ΔW is a weight change rate (unit %), Wf is a weight of a cured body after maintaining the cured body at 80° C. for 24 hours, and Wi is a weight of a cured body before maintaining the cured body at 80° C. for 24 hours.

[0035] The units of the weights (Wf and Wi) in Equation 1 are not limited as long as the same units are applied to each other.

[0036] The upper limit of the weight change rate (ΔW) may be about 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.9%, 0.8%, 0.7%, 0.6%, or 0.5%, and the lower limit thereof may be about 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, or 0.7%. The weight change rate may be in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0037] The above weight change rate can be achieved even when the solidified body contains non-encapsulated PCM. As described above, PCM can absorb heat and become a liquid phase, thereby being lost, so that in some cases, PCM is encapsulated and used to solve such problems. When the PCM is properly encapsulated, the PCM becomes a liquid phase, and leakage of the liquid PCM can be prevented by capsules. However, since encapsulation reduces the efficiency of heat transfer to the PCM, the desired latent heat characteristics cannot be ensured, or an excess of PCM must be used to ensure the latent heat characteristics, wherein the use of an excess of PCM may cause other problems (e.g., difficulty in controlling viscosity, deterioration of injection characteristics, etc.). However, according to the method disclosed herein, even non-encapsulated PCM can be stably maintained in the solidified body.

[0038] For example, based on the total weight of the PCM contained in the composition or the cured body, the upper limit of the ratio of the encapsulated PCM may be about 10 wt%, 9 wt%, 8 wt%, 7 wt%, 6 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, 0.5 wt%, 0.1 wt%, 0.05 wt%, or 0.01 wt%, and the lower limit thereof may be about 0 wt%. The ratio may be in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0039] The latent heat characteristics or weight change rate of the cured body can also be achieved without applying a so-called composite material as a PCM. Although PCM exhibits heat absorption characteristics, it generally has a low thermal conductivity. Therefore, it is not easy to transfer the heat to be processed to the PCM. For this purpose, a composite material is known in which a material with high thermal conductivity (such as graphite or carbon fiber) is compounded with the PCM. Such a material can solve the problem of low thermal conductivity (which is a disadvantage of PCM) to some extent, but is disadvantageous in terms of weight reduction because it increases the density or specific gravity of the material. In the present application, the problem of reduced thermal control efficiency due to low thermal conductivity can be solved by selecting a curable resin component that forms the cured body, adjusting the degree of crosslinking, adjusting the type and ratio of the PCM, controlling the filler and / or adjusting the method for preparing the composition, without using a composite PCM, and thus a lightweight material can be provided.

[0040] The composition may include a resin component. The scope of the term resin component includes components that can form a resin through a curing reaction, etc., as well as components that are themselves recognized as resins in the industry. The resin component can be a monomer compound, an oligomer compound, or a polymer compound. The resin component can be a curable resin component. The term curable resin component can mean a resin component that can be cured.

[0041] The weight average molecular weight (Mw) of the curable resin component can be controlled. The weight average molecular weight can be measured by the method described in the "6.GPC (gel permeation chromatography)" section of the embodiment. The lower limit of the weight average molecular weight can be 9,000g / mol, 10,000g / mol, 15,000g / mol, 20,000g / mol, or 25,000g / mol or so, and its upper limit can be 100,000g / mol, 90,000g / mol, which can be about 80,000g / mol, 70,000g / mol, 60,000g / mol, 50,000g / mol, 40,000g / mol, or 30,000g / mol or so. The weight average molecular weight can be greater than or equal to, or greater than the range of any one of the above lower limits; or less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than the range of any one of the above lower limits. Such a curable resin component may form a network of a cured body in which the PCM may be stably retained.

[0042] As the resin component having the above molecular weight, a curable silicone component can be effectively applied. The type of the curable resin component is not particularly limited, but in terms of effectively ensuring the desired effect, a curable silicone component can be used as the curable resin component.

[0043] When the curable resin component is a curable silicone component, the component is an addition-curable silicone component that may include (1) a polyorganosiloxane containing two or more alkenyl groups in the molecule, and (2) a polyorganosiloxane containing two or more silicon-bonded hydrogen atoms in the molecule. The compounds may form a cured product by an addition reaction in the presence of a catalyst (e.g., a platinum catalyst).

[0044] (1) The polyorganosiloxane contains at least two alkenyl groups. In this case, specific examples of alkenyl groups include vinyl, allyl, butenyl, pentenyl, hexenyl or heptenyl, etc., and the aforementioned vinyl group is generally used, but is not limited thereto. In (1) the polyorganosiloxane, the bonding position of the above alkenyl group is not particularly limited. For example, the alkenyl group may be bonded to the end of the molecular chain and / or to the side chain of the molecular chain. In addition, in (1) the polyorganosiloxane, the types of substituents that may be included in addition to the above alkenyl groups may include: alkyl groups, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or heptyl; aryl groups, such as phenyl, tolyl, xylyl, or naphthyl; aralkyl groups, such as benzyl or phenethyl; and alkyl groups substituted with halogens, such as chloromethyl, 3-chloropropyl, or 3,3,3-trifluoropropyl, etc., and the aforementioned methyl or phenyl group is generally used, but is not limited thereto.

[0045] (1) The molecular structure of the polyorganosiloxane is not particularly limited, and it may have any shape, such as a linear, branched, cyclic, network or partially branched linear structure. Generally, polyorganosiloxane having a linear molecular structure among such molecular structures is usually used, but is not limited thereto.

[0046] More specific examples of the polyorganosiloxane (1) may include: a dimethylsiloxane-methylvinylsiloxane copolymer end-capped with a trimethylsiloxane group at both ends of the molecular chain, a methylvinylpolysiloxane end-capped with a trimethylsiloxane group at both ends of the molecular chain, a dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer end-capped with a trimethylsiloxane group at both ends of the molecular chain, a dimethylpolysiloxane end-capped with a dimethylvinylsiloxane group at both ends of the molecular chain, a methylvinylpolysiloxane end-capped with a dimethylvinylsiloxane group at both ends of the molecular chain, a dimethylsiloxane-methylvinylsiloxane copolymer end-capped with a dimethylvinylsiloxane group at both ends of the molecular chain, a dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer end-capped with a dimethylvinylsiloxane group at both ends of the molecular chain, and a polyorganosiloxane containing R 1 2SiO 2 / 2 The siloxane units represented by R 1 2R 2 SiO 1 / 2 The siloxane units represented by SiO4 / 2 A polyorganosiloxane copolymer containing a siloxane unit represented by R 1 2R 2 SiO 1 / 2 The siloxane units represented by SiO 4 / 2 A polyorganosiloxane copolymer containing a siloxane unit represented by R 1 R 2 SiO 2 / 2 The siloxane units represented by R 1 SiO 3 / 2 The siloxane unit represented by R 2 SiO 3 / 2 and mixtures of two or more of the foregoing, but are not limited thereto. 1 is a hydrocarbon group other than an alkenyl group, which may specifically be: an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or heptyl; an aryl group such as phenyl, tolyl, xylyl, or naphthyl; an aralkyl group such as benzyl or phenethyl; an alkyl group substituted with a halogen such as chloromethyl, 3-chloropropyl, or 3,3,3-trifluoropropyl, etc. In addition, herein, R 2 The alkenyl group may be vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl or the like.

[0047] In the addition-curable silicone composition, (2) polyorganosiloxane can be used to crosslink (1) polyorganosiloxane. In (2) polyorganosiloxane, the bonding position of hydrogen atoms is not particularly limited, for example, it can be bonded to the end and / or side chain of the molecular chain. In addition, in (2) polyorganosiloxane, the type of substituents that can be contained in addition to silicon-bonded hydrogen atoms is not particularly limited, and it can include, for example, alkyl, aryl, aralkyl or halogen-substituted alkyl as mentioned in (1) polyorganosiloxane, and the aforementioned methyl or phenyl group is generally used, but is not limited thereto.

[0048] (2) The molecular structure of the polyorganosiloxane is not particularly limited, and it may have any shape, such as a linear, branched, cyclic, network or partially branched linear structure. Generally, polyorganosiloxane having a linear molecular structure among such molecular structures is usually used, but is not limited thereto.

[0049] (2) More specific examples of the polyorganosiloxane may include: methylhydrogenpolysiloxane terminated with trimethylsiloxane groups at both ends of the molecular chain, dimethylsiloxane-methylhydrogen copolymer terminated with trimethylsiloxane groups at both ends of the molecular chain, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymer terminated with trimethylsiloxane groups at both ends of the molecular chain, dimethylpolysiloxane terminated with dimethylhydrogensiloxane groups at both ends of the molecular chain, dimethylsiloxane-methylphenylsiloxane copolymer terminated with dimethylhydrogensiloxane groups at both ends of the molecular chain, methylphenylpolysiloxane terminated with dimethylhydrogensiloxane groups at both ends of the molecular chain, 1 3SiO 1 / 2 The siloxane unit represented by R 1 2HSiO 1 / 2 The siloxane units represented by SiO 4 / 2 A polyorganosiloxane copolymer containing a siloxane unit represented by R 1 2HSiO 1 / 2 The siloxane units represented by SiO 4 / 2 A polyorganosiloxane copolymer containing a siloxane unit represented by R 1 HSiO 2 / 2 The siloxane units represented by R 1 SiO 3 / 2 Siloxane units represented by HSiO 3 / 2 and mixtures of two or more of the foregoing, but are not limited thereto. 1 It is a hydrocarbon group other than alkenyl, which specifically can be: alkyl, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, or heptyl; aryl, such as phenyl, tolyl, xylyl, or naphthyl; aralkyl, such as benzyl or phenethyl; alkyl substituted with halogen, such as chloromethyl, 3-chloropropyl, or 3,3,3-trifluoropropyl, etc.

[0050] The content of the (2) polyorganosiloxane is not particularly limited as long as the (2) polyorganosiloxane is contained to such an extent that appropriate curing can be achieved. For example, the (2) polyorganosiloxane may be contained in such an amount that 0.5 to 10 silicon-bonded hydrogen atoms are present per alkenyl group contained in the aforementioned (1) polyorganosiloxane. Within this range, curing can be sufficiently performed and heat resistance can be ensured.

[0051] The addition curable silicone component may also contain platinum or a platinum compound as a catalyst for curing. The specific type of such platinum or platinum compound is not particularly limited. The ratio of the catalyst may also be adjusted to a level that allows for proper curing.

[0052] In another example, the curable silicone component is a condensation-curable silicone component, which may include: for example, (a) an alkoxy-containing siloxane polymer; and (b) a hydroxyl-containing siloxane polymer.

[0053] The (a) siloxane polymer may be, for example, a compound represented by Formula 1 below.

[0054] [Formula 1]

[0055] R 1 a R 2 b SiO c (OR 3 ) d

[0056] In formula 1, R 1 and R 2 Each independently represents a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group, R 3 represents an alkyl group, wherein if there are multiple R 1 , R 2 and R 3 , then they may be the same as or different from each other, and a and b each independently represent a number that is 0 or greater and less than 1, a+b represents a number that is greater than 0 and less than 2, c represents a number that is greater than 0 and less than 2, d represents a number that is greater than 0 and less than 4, and a+b+c×2+d is 4.

[0057] In the definition of Formula 1, the monovalent hydrocarbon group may be, for example, an alkyl group having 1 to 8 carbon atoms, a phenyl group, a benzyl group, or a tolyl group, etc., wherein the alkyl group having 1 to 8 carbon atoms may be a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, or an octyl group, etc. In addition, in the definition of Formula 1, the monovalent hydrocarbon group may be substituted by, for example, a known substituent such as a halogen, an amino group, a mercapto group, an isocyanate group, a glycidyl group, a glycidyloxy group, or a urea group.

[0058] In the definition of formula 1, R 3 Examples of the alkyl group in may include methyl, ethyl, propyl, isopropyl, or butyl, etc. Among the alkyl groups, methyl or ethyl, etc. are generally applied, but are not limited thereto.

[0059] In the polymer of Formula 1, a branched or tertiary crosslinked siloxane polymer may be used. In addition, in the (a) siloxane polymer, a hydroxyl group may remain within a range not impairing the purpose, specifically, within a range not inhibiting the dealcoholization reaction.

[0060] The (a) siloxane polymer can be produced, for example, by hydrolyzing and condensing a polyfunctional alkoxysilane or a polyfunctional chlorosilane, etc. A person skilled in the art can easily select an appropriate polyfunctional alkoxysilane or chlorosilane according to the desired (a) siloxane polymer, and can also easily control the conditions of the hydrolysis and condensation reaction using the same. Meanwhile, when producing the (a) siloxane polymer, an appropriate monofunctional alkoxysilane may also be used in combination according to the purpose.

[0061] As (a) the siloxane polymer, for example, commercially available organosiloxane polymers such as X40-9220 or X40-9225 of Shin-Etsu Silicone, XR31-B1410, XR31-B0270 or XR31-B2733 of GE Toray Silicones, and the like can be used.

[0062] As the (b) hydroxyl-containing siloxane polymer contained in the condensation-curable silicone composition, for example, a compound represented by the following Formula 2 may be used.

[0063] [Formula 2]

[0064]

[0065] In Formula 2, R4 and R5 each independently represent a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group, wherein if a plurality of R4 and R5 each exist, they may be the same as or different from each other, and n represents an integer of 5 to 2,000.

[0066] In the definition of Formula 2, specific types of the monovalent hydrocarbon group may include, for example, the same hydrocarbon groups as in the case of Formula 1.

[0067] (b) siloxane polymers can be produced, for example, by hydrolyzing and condensing dialkoxysilanes and / or dichlorosilanes. One of ordinary skill in the art can easily select suitable dialkoxysilanes or dichlorosilanes according to the desired (b) siloxane polymer, and can also easily control the conditions of the hydrolysis and condensation reactions using them. As (b) siloxane polymers, for example, commercially available bifunctional organosiloxane polymers can be used, such as XC96-723, YF-3800 or YF-3804 of GE Toray Silicones.

[0068] The above-mentioned addition-curable or condensation-curable silicone composition is an example of the curable silicone component used in the present application.

[0069] The lower limit of the weight ratio of the curable resin component in the composition can be about 30 weight %, 35 weight %, 40 weight %, 45 weight %, or 50 weight %, and the upper limit can be about 80 weight %, 75 weight %, and 70 weight %, 65 weight %, 55 weight %, 50 weight %, or 45 weight %. The ratio can be greater than or equal to, or greater than any one of the above lower limits; less than or equal to, or less than any one of the above upper limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The ratio is based on the total weight of the solid content of the composition, and therefore when the composition contains a solvent, it is a ratio based on the total weight of the composition excluding the solvent.

[0070] The composition may include PCM (phase change material) to ensure latent heat properties. The latent heat properties may be exhibited by absorbing and / or releasing heat during the phase change process of the PCM. The phase change process of the PCM is an isothermal process.

[0071] The phase transition of PCM can be a phase transition from solid to solid, a phase transition from solid to liquid, a phase transition from solid to gas, or a phase transition from liquid to gas. The above phase transition can be an endothermic reaction. In terms of efficiency, a PCM having a phase transition from solid to liquid is advantageous, but such a PCM becomes a liquid phase after the phase transition, making it difficult to maintain in a solidified body. However, even if a PCM that can exist in a liquid phase is applied in a non-encapsulated state, the solidified body of the present application can also exhibit the above-mentioned weight change rate. Therefore, the PCM used in the present application can be a material in which a phase transition occurs between a solid phase and a liquid phase, and can be a material in which the phase transition reaction from a solid phase to a liquid phase can be an endothermic reaction.

[0072] The PCM may have a melting point within a predetermined range. The lower limit of the melting point of the PCM may be around 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, or 50°C, and the upper limit thereof may be around 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, or 45°C. The melting point may be within a range higher than or equal to, or higher than any of the above lower limits; within a range lower than or equal to, or lower than any of the above upper limits; or within a range lower than or equal to, or lower than any of the above upper limits and higher than or equal to, or higher than any of the above lower limits.

[0073] The lower limit of the latent heat zone starting temperature of the PCM may be about 5° C., 10° C., 15° C., or 20° C., and the upper limit thereof may be about 50° C., 45° C., 40° C., 35° C., 30° C., 25° C., or 20° C. The latent heat zone starting temperature may be in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0074] The lower limit of the latent heat zone end temperature of the PCM may be about 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., or 60° C., and the upper limit thereof may be about 200° C., 150° C., 100° C., 95° C., 90° C., 85° C., 80° C., 75° C., 70° C., 65° C., or 60° C. The latent heat zone end temperature may be in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0075] The width of the latent heat zone of the PCM (a value obtained by subtracting the latent heat zone start temperature from the latent heat zone end temperature) may have a lower limit of about 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., or 50° C., and an upper limit thereof may also be about 100° C., 95° C., 90° C., 85° C., 80° C., 75° C., 70° C., 65° C., 60° C., 55° C., 50° C., or 45° C. The width of the latent heat zone may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0076] The lower limit of the latent heat indicated by the PCM may be around 50 J / g, 60 J / g, 70 J / g, 80 J / g, 90 J / g, 100 J / g, 110 J / g, 120 J / g, 130 J / g, 140 J / g, 150 J / g, 160 J / g, 170 J / g, or 180 J / g, and the upper limit thereof may be around 400 J / g, 380 J / g, 360 J / g, 340 J / g, 320 J / g, 300 J / g, 280 J / g, 260 J / g, 240 J / g, 220 J / g, 200 J / g, 190 J / g, or 180 J / g. The latent heat may be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits.

[0077] By applying the PCM, a desired cured body can be formed.

[0078] As PCM, a known PCM can be applied as long as it exhibits the above-mentioned characteristics. As PCM, an inorganic material, an organic material, or a eutectic material is known. Among these materials, as a material having the above-mentioned latent heat characteristics, an organic PCM can be used.

[0079] As the organic PCM, fatty acids, alcohols (polyols), ketones, D-lactic acid, or paraffin-based materials are known, and in the present application, one of them, or a mixture of two or more thereof may be used.

[0080] Fatty acids can be exemplified by formic acid, n-octanoic acid, lauric acid, palmitic acid, stearic acid, etc.; alcohol-based PCMs can be exemplified by glycerol, polyethylene glycol (PEG), xylitol, or erythritol, etc.; and ketone-based PCMs can be exemplified by 2-pentadecanone or 4-heptadecanone, etc.

[0081] As PCM, paraffin-based materials can be used. As paraffin-based PCM, n-heptadecane, n-octadecane, n-nonadecane, n-eicosane, n-heneicosane, n-docosane, n-tricosane, n-pentacosane, n-hexacosane, n-heptacosane, n-octacosane, n-nonacosane, n-triacontane, n-triacontane, n-triacontane, n-triacontane, or other high-grade paraffins (paraffin C 16 ~C 18 、Paraffin C 13 ~C 24 , RT 35HC, paraffin C 16 ~C 28 、Paraffin C 20 ~C 33 、Paraffin C 22 ~C 45 、Paraffin C 22 ~C 50 , paraffin natural wax 811, paraffin natural wax 106, etc.).

[0082] An appropriate type may be selected from among known paraffin-based PCMs and used.

[0083] As PCM, paraffin wax having a melting point and a specific carbon number within the above range can be used. The lower limit of the carbon number of the paraffin wax can be about 5, 10, or 15, and the upper limit thereof can be about 60, 55, 50, 45, 40, 35, or 30. The carbon number of the paraffin wax can be in a range of less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits. Such paraffin wax can be an alkane having the above carbon number.

[0084] The lower limit of the weight ratio of PCM relative to 100 parts by weight of the curable resin component in the composition may be about 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 32 parts by weight, or 34 parts by weight, and the upper limit thereof may be about 60 parts by weight, 58 parts by weight, 56 parts by weight, 54 parts by weight, 52 parts by weight, 50 parts by weight, 48 parts by weight, 46 parts by weight, 44 parts by weight, 42 parts by weight, 40 parts by weight, 38 parts by weight, 36 parts by weight, 34 parts by weight, 32 parts by weight, 30 parts by weight, 28 parts by weight, or 26 parts by weight. The ratio may be in the range of greater than or equal to, or greater than any of the above lower limits; in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. Generally, as the content of PCM increases, the latent heat characteristics may also increase, but too much PCM may cause leakage problems and reduce the heat control efficiency of heat-generating products. Therefore, the upper limit of the appropriate PCM content may be adjusted in consideration of the application.

[0085] The composition may comprise fillers as further components.

[0086] Such a filler can prevent leakage of PCM, thereby serving to ensure that the weight change rate can be achieved. Although the reason is unclear, it is expected that the filler having a particle size distribution to be described below forms a structure (eg, a stacked structure or a network structure) capable of holding the PCM in the composition or cured body.

[0087] As the filler, a known filler can be applied without particular limitation, as long as it has a particle size distribution to be described below. In order to impart additional functions, a filler having flame retardancy (flame retardant particles) and / or a filler having thermal conductivity (thermal conductive particles) can be used as the filler. If the filler has flame retardancy, additional flame retardancy can be imparted to the cured body. In addition, the thermally conductive filler can allow the heat to be processed to be more efficiently transferred to the PCM.

[0088] The filler can be exemplified as, for example, one or more fillers selected from the following: aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), boehmite (AlOOH), hydromagnesite, magnesium oxide, aluminum oxide, aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), silicon carbide (SiC), zinc oxide (ZnO) and beryllium oxide (BeO), but is not limited thereto. One or two or more of the above fillers can be selected. When a low-density solidified body is to be formed, a filler with a small specific gravity (e.g., aluminum hydroxide or magnesium hydroxide, etc.) can be selected from the filler component.

[0089] The shape of the filler is not particularly limited, and for example, a spherical filler, a needle-shaped filler, a plate-shaped filler, or other amorphous fillers may be used.

[0090] The filler may have a particle size distribution in which the D10, D50, and / or D90 particle diameters are adjusted. The particle diameter is measured by the method described in the "2. Measurement of the average particle diameter of the filler" section in the Examples section of this specification. In the volume-based particle size distribution diagram obtained according to the above section, the particle diameter at the point where the cumulative volume is 10% is designated as the D10 particle diameter, the particle diameter at the point where the cumulative volume is 50% is designated as the D50 particle diameter, and the particle diameter at the point where the cumulative volume is 90% is designated as the D90 particle diameter.

[0091] The lower limit of the D50 particle diameter of the filler can be about 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm, and the upper limit can be about 200 μm, 180 μm, 160 μm, 140 μm, 120 μm, 100 μm, 80 μm, 60 μm, or 50 μm. The D50 particle diameter can be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0092] In the particle size distribution of the filler, the ratio of the filler's D50 particle diameter to the D10 particle diameter (A=D50 particle diameter / D10 particle diameter) may be greater than the ratio of the filler's D90 particle diameter to the D50 particle diameter (B=D90 particle diameter / D50 particle diameter) (A>B).

[0093] For example, the ratio of the D50 particle diameter to the D10 particle diameter (A=D50 particle diameter / D10 particle diameter) may have a lower limit of about 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, or 10, and an upper limit thereof may be about 30, 28, 26, 24, 22, 20, 18, 16, 14, 12, 11, 10.5, or 10. The ratio may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0094] For example, the upper limit of the ratio of the filler's D90 particle diameter to the D50 particle diameter (B = D90 particle diameter / D50 particle diameter) may be about 7, 6.5, 6, 5.5, 5, 4.5, 4, 3.5, 3, 2.5, or 2, and the lower limit thereof may be about 1, 1.2, 1.4, 1.6, or 1.8. The ratio may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0095] For example, the upper limit of the ratio of the D90 particle diameter of the filler to the D10 particle diameter (C=D90 particle diameter / D10 particle diameter) may be about 50, 45, 40, 35, 30, 25, or 20, and the lower limit thereof may be about 5, 10, 15, 16, 17, or 18. The ratio may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0096] The ratio (C / B) between the ratio C (=D90 particle diameter / D10 particle diameter) and the ratio B (=D90 particle diameter / D50 particle diameter) may also be adjusted. The lower limit of the ratio (C / B) may be about 1, 2, 3, 4, 5, 6, 7, 8, 9, 9.5, or 10, and the upper limit thereof may be about 30, 28, 26, 24, 22, 20, 18, 16, 14, 12, 11, 10.5, or 10. The ratio (C / B) may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0097] The ratio (A / B) between the ratio A (=D50 particle diameter / D10 particle diameter) and the ratio B (=D90 particle diameter / D50 particle diameter) may also be adjusted. The lower limit of the ratio (A / B) may be about 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or 5.5, and the upper limit thereof may be about 20, 18, 16, 14, 12, 10, 8, or 6. The ratio (A / B) may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0098] The ratio (C / A) between the ratio A (=D50 particle diameter / D10 particle diameter) and the ratio C (=D90 particle diameter / D10 particle diameter) may also be adjusted. The lower limit of the ratio (A / B) may be about 0.01, 0.05, 0.1, 0.5, 1, or 1.5, and the upper limit thereof may be about 10, 9, 8, 7, 6, 5, 4, 3, or 2. The ratio (C / A) may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0099] Under the above particle size distribution, leakage of PCM and the like can be appropriately prevented, and desired functions can be ensured.

[0100] In one example, fillers may be included such that the ratio (P / F) of the weight of fillers (F) to the weight of PCM (P) is within a predetermined range. For example, the upper limit of the ratio P / F may be about 0.45, 0.44, 0.43, 0.42, 0.41, 0.40, 0.39, 0.38, 0.37, 0.36, or 0.35, and the lower limit thereof may be about 0.1, 0.15, 0.2, 0.25, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.4. The ratio may be within a range greater than or equal to, or greater than any of the above lower limits; within a range less than or equal to, or less than any of the above upper limits; or within a range less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits.

[0101] In the composition, the upper limit of the ratio of the filler relative to 100 parts by weight of the curable resin component can be about 300 parts by weight, 280 parts by weight, 260 parts by weight, 240 parts by weight, 220 parts by weight, 200 parts by weight, 180 parts by weight, 160 parts by weight, 140 parts by weight, 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, or 75 parts by weight, and the lower limit thereof can also be about 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, or 100 parts by weight. The ratio may be within a range greater than or equal to, or greater than any of the above lower limits; within a range less than or equal to, or less than any of the above upper limits; or within a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0102] In the composition, the upper limit of the ratio of the filler relative to 100 parts by weight of PCM may be about 1,000 parts by weight, 950 parts by weight, 900 parts by weight, 850 parts by weight, 800 parts by weight, 750 parts by weight, 700 parts by weight, 650 parts by weight, 600 parts by weight, 550 parts by weight, 500 parts by weight, 450 parts by weight, 400 parts by weight, 350 parts by weight, 300 parts by weight, 280 parts by weight, or 260 parts by weight, and the lower limit thereof may be about 50 parts by weight, 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, 260 parts by weight, 270 parts by weight, 275 parts by weight, or 280 parts by weight. The ratio may be in a range of greater than or equal to, or greater than any of the above lower limits; in a range of less than or equal to, or less than any of the above upper limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0103] In addition to the above components, the composition may also include other necessary components. For example, in addition to the above components, if necessary, the composition may also include other additives, such as catalysts, hollow fillers, pigments or dyes, dispersants, thixotropy imparting agents, and / or flame retardants, etc.

[0104] Such a composition may be a solvent-based composition, an aqueous composition, or a solvent-free composition, and may suitably be a solvent-free composition.

[0105] The term solvent-free composition refers to a composition that does not substantially contain a solvent. For example, the upper limit of the ratio of the solvent contained in the composition can be about 10 wt %, 9 wt %, 8 wt %, 7 wt %, 6 wt %, 5 wt %, 4 wt %, 3 wt %, 2 wt %, 1 wt %, 0.5 wt %, 0.1 wt %, 0.05 wt % or 0.01 wt %, and its lower limit can be about 0 wt %. The ratio can be in a range of less than or equal to or less than any one of the above-mentioned upper limits; or in a range of less than or equal to or less than any one of the above-mentioned upper limits and greater than or equal to or greater than any one of the above-mentioned lower limits.

[0106] As described above, the curable composition may be a one-component composition or a two-component composition, and in some cases, it may be the main agent part or the curing agent part of a two-component composition, or a mixture of the main agent part and the curing agent part.

[0107] When the composition is a two-component composition, the ratio of other components in the main agent part and the curing agent part except the curable resin component is not particularly limited. For example, PCM and / or filler can be included in both the main agent part and the curing agent part, or can be included in the main agent part and the curing agent part separately.

[0108] The composition is suitable for various applications, and in particular, it is applied to heat-generating products, whereby it can be used as a material for controlling heat of the product.

[0109] In one example, a method for preparing the composition may be selected in order to satisfy the latent heat characteristics and weight change rate, etc., as described above.

[0110] For example, the composition may be prepared by mixing the PCM, the curable resin component, and the filler in a state where the PCM is melted. Through this step, a desired composition may be provided more efficiently.

[0111] The method for preparing the composition may include the step of mixing the PCM in a molten state with a curable resin component and a filler. For example, the preparation method may include a first step of melting the PCM and a second step of mixing the molten PCM with the curable resin component and the filler.

[0112] The method of melting the PCM is not particularly limited, for example, the PCM may be maintained at a temperature higher than the melting point of the PCM to be melted. In one example, the lower limit of the difference (T-Tm) between the holding temperature (T) of the PCM and the melting point (Tm) of the PCM may be about 10°C, 15°C, 20°C, 25°C, or 30°C, and the upper limit thereof may be about 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, or 30°C. The difference (T-Tm) may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0113] By mixing the PCM melted within this temperature range with a curable resin component and a filler to prepare a composition, a composition having desired properties can be efficiently prepared. The temperature when the molten PCM and the curable resin component are mixed may be a temperature in the same range as the temperature when the PCM is melted, or a temperature lower than the temperature.

[0114] In one example, the lower limit of the difference (Tx-Tm) between the mixing temperature (Tx) and the melting point (Tm) of the PCM may be about 10° C., 15° C., 20° C., 25° C., or 30° C., and the upper limit thereof may be about 100° C., 95° C., 90° C., 85° C., 80° C., 75° C., 70° C., 65° C., 60° C., 55° C., 50° C., 45° C., 40° C., 35° C., or 30° C. The difference (Tx-Tm) may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0115] This specification discloses a cured body of the composition. There is no restriction on the method for curing the composition to obtain a cured body, and a suitable curing method is applied according to the type of the composition. For example, the following method can be used: a method of irradiating the composition with an energy beam (such as ultraviolet light) in the case of an energy beam curing type; a method of keeping the composition under appropriate moisture in the case of a wet curing type; a method of applying appropriate heat to the composition in the case of a heat curing type; a method of keeping the composition at room temperature in the case of a room temperature curing type; a method of applying two or more curing methods in the case of a mixed curing type; and the like. As described above, in a suitable example, the composition can be a room temperature curing type.

[0116] This specification also discloses a product (heat-generating product) comprising the composition or its cured body. The composition or its cured body can be usefully applied as a material for controlling the heat of a heating component, a heating element, or a heating product. Therefore, the article can include a heating component, a heating element, or a heating product. A heating component, an element, or a product means a component, an element, or a product that generates heat during use, and its type is not particularly limited. Representative heating components, elements, or products include various electrical / electronic products including battery cells, battery modules, or battery packs, etc.

[0117] The article of the present application may include, for example, a heat-generating component, element, or product, and a composition (or a two-component composition) or a cured body thereof that is adjacent to the heat-generating component, etc. In this case, as described above, the heat-generating component, element, or product may be a component, element, or product having an appropriate driving temperature in the range of about 15° C. to 60° C. That is, the composition of the present application may be used to be disposed adjacent to the heat-generating component, element, or product to uniformly maintain the driving temperature of the product within the above range.

[0118] The specific method of constituting the article is not particularly limited, and the article may be configured in various known methods as long as the composition or two-component composition of the present application or a cured body thereof is applied as a heat dissipation material.

[0119] In one example, the composition can be used as a potting material when constructing a battery module or a battery pack. The potting material can be a material that covers at least a portion or all of a plurality of unit battery cells in a battery module or a battery pack and is in contact with it at the same time. When the composition of the present application or its cured body is applied as a potting material, it can control the heat generated in the battery cell of the battery module or battery pack, can prevent chain fire or explosion, etc., and can evenly maintain the driving temperature of the module, group or battery cell. The present application can also provide a composition with excellent potting efficiency, because the viscosity or thixotropy is controlled to an appropriate level before curing, and a stable potting structure is formed after curing without generating unnecessary bubbles. The present application can provide such a composition: it can provide a battery module or battery pack with high power while being light in weight compared to the volume by showing a low density after curing. The present application can also provide a composition with excellent desired physical properties (including insulation, etc.).

[0120] In this case, with respect to battery-related technologies, the composition can be applied as a heat dissipation material for a battery module or battery pack, etc., or as a heat dissipation material for an OBC (on-board charger) for a vehicle. Therefore, the present application may also relate to a battery module, a battery pack or an on-board charger (OBC) comprising the composition or a solidified body thereof as a heat dissipation material. In a battery module, a battery pack or an on-board charger, the application position or application method of the composition or solidified body is not particularly limited, and known methods can be applied. In addition, the composition of the present application is not limited to the above uses, and it can be effectively applied to various uses requiring excellent heat dissipation characteristics, storage stability and adhesion.

[0121] In another example related to the present application, the present application may relate to an electronic device or apparatus having a cured body of the composition.

[0122] The type of electronic device or apparatus is not particularly limited, and may be exemplified by, for example, an AVN (audio video navigation) for a vehicle, or an OBC (on-board charger) module, an LED module or an IC chip for an electric vehicle, and a computer or mobile device including the same.

[0123] The cured body of the composition can dissipate heat within a device or apparatus, and can impart durability against impact, insulation, and the like.

[0124] In one example, the composition can be used as a battery potting material.

[0125] The present application also relates to a battery module using the potting material. Such a battery module can exhibit high power while being light in weight compared to the same volume, wherein heat generated from battery cells and the like is properly controlled and problems such as chain fire do not occur.

[0126] The battery module may include a plurality of battery cells; and the composition or a cured product thereof covering at least a portion or all of the plurality of battery cells. In one example, the battery module may further include a module housing or a substrate, and the battery cells may be disposed in the module housing or on the substrate.

[0127] In one example, the composition or a cured product thereof (potting material) may cover the battery cells while being in contact with the entire surface of the plurality of battery cells (except for the surface of the battery cells in contact with the substrate side). Figure 1 structure), or may only contact the upper portion of a plurality of battery cells ( Figure 2 structure).

[0128] Figure 1 and Figure 2is a schematic diagram of such a battery module structure, and is a diagram showing a structure including a substrate 10, a battery cell 20, and a potting material 30 (the composition or a cured product thereof). The battery module may further include an adhesive material 40 for fixing the battery cell 20 to the substrate 10, and in one example, the adhesive material 40 may be formulated to have thermal conductivity.

[0129] If the composition or a cured product thereof is applied as a potting material, a specific configuration of a battery module (eg, types of battery cells, substrates, and / or adhesive materials) is not particularly limited, and known materials may be applied.

[0130] For example, a known cylindrical battery cell may be applied as the battery cell, and a known material may also be applied as the substrate or the binder material.

[0131] The manufacturing method of the battery module is not particularly limited, and for example, it may be formed by pouring the composition onto the upper portion of a plurality of battery cells formed on a substrate, and curing it if necessary.

[0132] Beneficial Effects

[0133] The present application provides a composition, and in one example, the composition can be used as a potting material when constructing a battery module or a battery pack. The potting material can be a material that covers at least a portion or all of a plurality of unit battery cells in a battery module or a battery pack while in contact with it. The present application can provide such a composition: it has excellent heat insulation and heat shielding properties, and exhibits flame retardancy, so that when it is applied as a potting material, the heat generated from the battery cells of the battery module or battery pack can be controlled, and chain fire can be prevented. The present application can also provide a composition with excellent potting efficiency, because the viscosity or thixotropy is controlled to an appropriate level before curing, and a stable potting structure is formed after curing without generating unnecessary bubbles. The present application can provide such a composition: it can provide a battery module or battery pack that is light in weight compared to the volume after curing by exhibiting a low density. The present application can also provide a composition with excellent desired physical properties (including insulation, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0134] Figure 1 and Figure 2 is a schematic diagram of an exemplary battery module of the present application.

[0135] Figure 3 is a diagram showing the arrangement of battery cells in a module applied to chain fire and rapid charge-discharge tests. DETAILED DESCRIPTION

[0136] Hereinafter, the present application will be described in detail through examples and comparative examples, but the scope of the present application is not limited to the following examples.

[0137] 1. Latent heat measurement

[0138] The latent heat is evaluated in the following manner. The main agent part and the curing agent part of each two-component composition of the embodiment or comparative example are placed in a two-component barrel and kept in a room at 50°C for about 1 hour. Thereafter, the composition is applied to an aluminum pan to a thickness of about 10 mm using a two-component syringe and cured by keeping it at room temperature (about 25°C) for about 24 hours. Subsequently, 3 mg of the solidified body is collected as a sample, and a DSC (differential scanning calorimeter) device (TA instrument, Q200 type) is used to evaluate the latent heat. When evaluating the latent heat, the temperature zone is set to -20°C to 200°C, the endothermic zone is measured while the temperature is increased at a rate of about 10°C / minute, and the latent heat (unit: J / g) is calculated by integrating the endothermic peak. In addition, the temperature at the inflection point of the endothermic peak at the left starting point of the endothermic peak is set as the latent heat zone starting temperature, and the temperature at the inflection point of the endothermic peak at the right starting point is set as the latent heat zone end temperature.

[0139] The latent heat is obtained by integrating the endothermic peak in the region between the latent heat region start temperature and the latent heat region end temperature.

[0140] 2. Measurement of the average particle diameter of fillers

[0141] According to ISO-13320 standard, the average particle diameter of the filler is measured using Marvern's Mastersizer 3000 equipment. During the measurement, ethanol is used as a solvent. The particle diameter can be obtained by analyzing the intensity and directivity values ​​of the laser scattered by the filler dispersed in the solvent via Mie theory. Through the above analysis, a volume-based particle size distribution diagram is obtained by converting into the diameter of a sphere with the same volume as the dispersed filler, and the particle diameter at the point where the cumulative volume is 10% is set to the D10 particle diameter, the particle diameter at the point where the cumulative volume is 50% is set to the D50 particle diameter, and the particle diameter at the point where the cumulative volume is 90% is set to the D90 particle diameter. In this specification, in the absence of special mention, the particle diameter referred to as the average particle diameter is the D50 particle diameter in the above particle diameters.

[0142] 3. Chain fire test

[0143] The 21700 standard (21 mm × 70 mm) cylindrical battery cells are Figure 3 Arranged in a honeycomb arrangement. Figure 3In the above arrangement, the gap between the battery cells is set to about 1 mm. A temperature measuring device (thermocouple) is attached to Figure 3 The battery cells 1 to 8, 14, 27 and 36 in the embodiment are fixed to the lower fixture. Thereafter, each composition prepared in the embodiment or the comparative example is potted to cover all arranged cylindrical battery cells and kept at room temperature (about 25°C) for about 24 hours to solidify, thereby manufacturing a battery module. Thereafter, in a state where battery cells 1 to 7 are overcharged, each of battery cells 1 to 7 is subjected to nail penetration to ignite it. Nail penetration is a test in which a sharp iron is pierced into a battery cell and the iron penetrates the battery cell. In the case where only battery cells 1 to 7 are ignited in the nail penetration and the fire does not spread to other surrounding battery cells, it is evaluated as OK, and if the fire spreads to other battery cells, it is evaluated as NG.

[0144] 4. Rapid charge-discharge test

[0145] The test was conducted using a battery module manufactured in the same manner as in the case of the chain fire test. Figure 3 The maximum temperature of the temperatures measured in battery cells 1 to 7 was recorded during the process of charging battery cells 1 to 7 to 100% for 30 minutes and then discharging for 15 minutes (conditions: maximum load 87A (3C), cutoff 0.582A (0.02C), cutoff voltage: 42V (4.15V to 3.0V, based on battery cell)).

[0146] 5. Is the surface solidified?

[0147] In the manufacturing process of the battery module applied to the chain fire test, the composition is potted and then kept at room temperature for about 5 minutes, and the fluidity is evaluated when the battery module is turned over. When the module is turned over, the case where the composition does not flow is evaluated as OK, and the case where the composition flows is evaluated as NG.

[0148] 6. GPC (Gel Permeation Chromatography)

[0149] The molecular weight characteristics of the material were measured using GPC (Gel permeation chromatography). The material to be analyzed was placed in a 5 mL vial and diluted to a concentration of approximately 5 mg / mL in toluene. Thereafter, the standard sample for calibration and the material to be analyzed were filtered through a syringe filter (pore size: 0.45 μm) and then measured. As the analysis program, ChemStation of Agilent technologies was used, and the elution time of the sample was compared with the calibration curve to obtain the weight-average molecular weight (Mw) or number-average molecular weight (Mn). The measurement conditions of GPC are as follows.

[0150] <GPC measurement conditions>

[0151] Instrument: 1200 series of Agilent technologies

[0152] Column: 2 PLgel mixed Bs of Polymer laboratories were used

[0153] Solvent: Toluene

[0154] Column temperature: 40 °C

[0155] Sample concentration: 5 mg / mL, 10 μL injection

[0156] Standard sample: Polystyrene (Mp: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)

[0157] 7. Viscosity evaluation

[0158] The viscosity was measured using a viscometer (Brookfield, Brookfield LV type) and rotor #63. After adjusting the zero point of the viscometer, the rotor was installed on the rotor connection part, the plate was installed on the plate connection part, and then it was adjusted by the adjusting rod to create a certain gap between the rotor and the plate. The plate was separated from it, approximately 0.5 mL of the viscosity measurement target was applied to the center of the separated plate, then the plate was installed on the plate connection part, and after waiting until the torque value became 0, the viscosity was measured at a rotational speed of approximately 60 °C and 10 rpm. The viscosity was measured for about 1 minute or longer, and the stable value was adopted.

[0159] 8. Liquid injection characteristics evaluation

[0160] 137 21700 standard (21mm×70mm) cylindrical battery cells are arranged in a honeycomb structure (the gap between the battery cells is 1mm). A simple module is manufactured by fixing each battery cell to the lower plate using epoxy glue and covering the upper frame. The curable composition (a mixture of the main agent part and the curing agent part) is injected into the simple module (using a two-component cartridge and a static mixer), and the injection form is observed. When the injection proceeds smoothly and an amount equivalent to the volume of the space between the battery cells in the simple module is injected, it is evaluated as OK, and when problems such as curing of the curable composition occur during the injection or the volume of the injected curable composition is significantly smaller than the volume of the space between the battery cells, it is evaluated as NG.

[0161] 9. Leakage Assessment

[0162] Leakage is evaluated in the following manner. A mixture is prepared by mixing the main agent part and the curing agent part of the curable composition in a weight ratio of 1: 1. The mixture is kept in a room at 80°C for about 1 hour, and then applied to an aluminum plate to a thickness of about 10 mm using a syringe. The applied mixture is kept at room temperature (about 25°C) for 24 hours to cure it, thereby manufacturing a cured body. The cured body is cut into squares with a horizontal length and a vertical length of 1 cm respectively to prepare a sample (weight: Wi, unit g). The sample is kept in a room at about 80°C for about 24 hours in a state placed on filter paper, and then taken out, thereby measuring the weight of the sample again (weight: Wf, unit g). The weight change rate (ΔW) is calculated by substituting the weight measured in the above process into the following equation 1. The weight change rates of four samples formed by the same curable composition are measured respectively, and the average value is taken.

[0163] [Equation 1]

[0164] ΔW=100×(Wf-–Wi) / Wi

[0165] If the weight change rate is less than 1%, it is evaluated as OK, and if it is 1% or more, it is evaluated as NG.

[0166] Example 1.

[0167] Preparation of the main agent

[0168] As the curable resin component, a curable silicone component (KCC, SL3000) was used. The main component (SL3000A) of the resin component, PCM (paraffin wax with a melting point in the range of about 42°C to 44°C (paraffin C 16 ~C 28, manufactured by Junsei)) and aluminum hydroxide (KC, DH-50P) are mixed to prepare the main agent part. The weight average molecular weight (Mw) of the main agent component (SL3000A) is about 28,000 g / mol, and PCM shows a latent heat of about 180 J / g in a temperature range of 20°C to 60°C in DSC analysis. Aluminum hydroxide has a D10 particle diameter of about 5 μm, a D50 particle diameter of about 50 μm, and a D90 particle diameter of about 90 μm.

[0169] During mixing, the main agent component (SL3000A) (A), PCM (B) and aluminum hydroxide (C) are mixed in a weight ratio (A:B:C) of about 100:32:80. When preparing the main agent part, the PCM is first melted while being uniformly stirred (300rpm) at a temperature of about 60°C for 1 hour, and the other components of the main agent part are mixed into the molten PCM, and further stirred at 500rpm for 2 hours. The mixing of PCM and the other components of the main agent part is carried out at a temperature of about 60°C. Thereafter, the mixture is stirred and defoamed for 20 minutes under a vacuum atmosphere and 50rpm to prepare the main agent part.

[0170] Preparation of curing agent

[0171] The curing agent part is prepared by mixing the curing agent component (SL3000B) of the curable resin component (manufactured by KCC, SL3000), PCM and aluminum hydroxide. The PCM and aluminum hydroxide used are the same as those used when preparing the main agent part. The weight average molecular weight (Mw) of the curing agent (SL3000B) is about 28,000 g / mol. When mixing, the curing agent component (SL3000B) (A), PCM (B) and aluminum hydroxide (C) are mixed in a weight ratio (A:B:C) of about 100:32:80. When preparing the curing agent part, the PCM is first uniformly stirred (300rpm) for 1 hour at a temperature of about 60°C to melt it, and the other components of the curing agent part are mixed into the molten PCM, and further stirred at 500rpm for 2 hours. The mixing of the PCM and the other components of the curing agent part is carried out at a temperature of about 60°C. Thereafter, the mixture is stirred and defoamed for 20 minutes at 50rpm in a vacuum atmosphere.

[0172] Composition

[0173] The composition is prepared by preparing a main agent part and a curing agent part separately. At this time, when the main agent part and the curing agent part are mixed, the main agent component (SL3000A) of the main agent part and the curing agent component (SL3000B) of the curing agent part are prepared to be mixed in a weight ratio of 1:1.

[0174] Example 2.

[0175] The main agent part was prepared in the same manner as in Example 1, except that the mixing ratio of the main agent component (SL3000A) (A), PCM (B) and aluminum hydroxide (C) was set to a weight ratio (A:B:C) of about 100:25:72. In addition, the curing agent part was prepared in the same manner as in Example 1, except that the curing agent component (SL3000B) (A), PCM (B) and aluminum hydroxide (C) were mixed in a weight ratio (A:B:C) of about 100:25:72. A composition was prepared using the main agent part and the curing agent part in the same manner as in Example 1.

[0176] Example 3.

[0177] The main agent part was prepared in the same manner as in Example 1, except that the mixing ratio of the main agent component (SL3000A) (A), PCM (B) and aluminum hydroxide (C) was set to a weight ratio (A:B:C) of about 100:35:100. In addition, the curing agent part was prepared in the same manner as in Example 1, except that the curing agent component (SL3000B) (A), PCM (B) and aluminum hydroxide (C) were mixed in a weight ratio (A:B:C) of about 100:35:100. A composition was prepared in the same manner as in Example 1 using the main agent part and the curing agent part.

[0178] Comparative Example 1.

[0179] Preparation of the main agent

[0180] As a curable resin component, a curable polyurethane component (Lord's circalok 6410) is used. The main agent component, PCM and aluminum hydroxide of the resin component are mixed to prepare the main agent part. The same PCM and aluminum hydroxide as in Example 1 are used. When mixing, the main agent component (A), PCM (B) and aluminum hydroxide (C) are mixed in a weight ratio (A:B:C) of about 100:25:72. When preparing the main agent part, the PCM is first melted while being uniformly stirred (300rpm) for 1 hour at a temperature of about 60°C, and the other components of the main agent part are mixed into the molten PCM, and further stirred at 500rpm for 2 hours. The mixing of PCM and other components of the main agent part is carried out at a temperature of about 60°C. Thereafter, the mixture is stirred and defoamed for 20 minutes at 50rpm in a vacuum atmosphere to prepare the main agent part.

[0181] Preparation of curing agent

[0182] The curing agent part is prepared by mixing the curing agent component of the curable polyurethane component (circalok 6410 of Lord), PCM and aluminum hydroxide (Sigma Aldrich). The PCM and aluminum hydroxide used are the same as those used when preparing the main agent part. When mixing, the curing agent component (A), PCM (B) and aluminum hydroxide (C) are mixed in a weight ratio (A:B:C) of about 100:25:72. When preparing the curing agent part, first, the PCM is uniformly stirred (300rpm) for 1 hour at a temperature of about 60°C to melt it, and the other components of the curing agent part are mixed into the molten PCM, and further stirred at 500rpm for 2 hours. The mixing of the PCM and the other components of the curing agent part is carried out at a temperature of about 60°C. Thereafter, the mixture is stirred and defoamed for 20 minutes under the condition of 50rpm in a vacuum atmosphere.

[0183] Composition

[0184] The composition is prepared by separately preparing a main agent part and a curing agent part. At this time, when the main agent part and the curing agent part are mixed, the main agent component of the main agent part and the curing agent component of the curing agent part are prepared to be mixed in a weight ratio of 1:1.

[0185] Comparative Example 2.

[0186] The main agent part, the curing agent part and the composition were prepared in the same manner as in Example 1, except that aluminum hydroxide was not applied when preparing the main agent part and the curing agent part.

[0187] Comparative Example 3.

[0188] The main agent part, the curing agent part and the composition were prepared in the same manner as in Example 1, except that aluminum hydroxide and PCM were not applied when preparing the main agent part and the curing agent part.

[0189] Comparative Example 4.

[0190] The main agent part was prepared in the same manner as in Example 1, except that the mixing ratio of the main agent component (SL3000A) (A), PCM (B) and aluminum hydroxide (C) was mixed to a weight ratio (A:B:C) of about 100:42:85. In addition, the curing agent part was prepared in the same manner as in Example 1, except that the curing agent component (SL3000B) (A), PCM (B) and aluminum hydroxide (C) were mixed in a weight ratio (A:B:C) of about 100:42:85. A composition was prepared using the main agent part and the curing agent part in the same manner as in Example 1.

[0191] Comparative Example 5.

[0192] The main agent part was prepared in the same manner as in Example 1, except that the mixing ratio of the main agent component (SL3000A) (A), PCM (B) and aluminum hydroxide (C) was mixed to a weight ratio (A:B:C) of about 100:18:70. In addition, the curing agent part was prepared in the same manner as in Example 1, except that the curing agent component (SL3000B) (A), PCM (B) and aluminum hydroxide (C) were mixed in a weight ratio (A:B:C) of about 100:18:70. A composition was prepared in the same manner as in Example 1 using the main agent part and the curing agent part.

[0193] Comparative Example 6.

[0194] Aluminum hydroxide (KC, SH-15k) of a different type from the aluminum hydroxide (KC, DH-50P) used in Example 1 was used. The aluminum hydroxide (KC, SH-15k) had a D10 particle diameter of about 2 μm, a D50 particle diameter of about 15 μm, and a D90 particle diameter of about 70 μm. A main agent part, a curing agent part, and a composition were prepared in the same manner as in Example 1, except that the aluminum hydroxide was used.

[0195] The evaluation results of the compositions of Examples and Comparative Examples are summarized and described in Tables 1 and 2 below. In Tables 1 and 2 below, the rapid charge-discharge test temperature is recorded as the highest temperature among the temperatures measured in the battery cells 1 to 7 during the above 4. Rapid charge-discharge test. In addition, the viscosity in Tables 1 and 2 below is the viscosity measured immediately after mixing the main agent part and the curing agent part of the curable composition at a weight ratio of 1:1.

[0196] [Table 1]

[0197]

[0198] [Table 2]

[0199]

Claims

1. A composition comprising: Silicone resin component; Phase change materials; and filler, wherein the composition is formulated to form a cured body exhibiting a latent heat of 20 J / g or greater, and wherein the weight change rate of the solidified body after the solidified body is maintained at 80° C. for 24 hours is less than 1%.

2. The composition of claim 1, wherein the phase change material exhibits a latent heat in the range of 100 J / g to 400 J / g in the temperature range of 20°C to 100°C.

3. The composition of claim 1, wherein the phase change material is a non-encapsulated phase change material. The composition according to claim 1 , wherein the phase change material is paraffin wax.

5. The composition of claim 1, wherein the filler is flame retardant particles. 6 . The composition of claim 1 , wherein the filler has a particle size distribution in which the D50 particle diameter is in the range of 20 μm to 200 μm. 7 . The composition according to claim 6 , wherein a ratio of a D50 particle diameter of the filler to a D10 particle diameter is greater than a ratio of a D90 particle diameter of the filler to a D50 particle diameter. 8 . The composition of claim 6 , wherein the ratio of the D50 particle diameter of the filler to the D10 particle diameter is in the range of 1.5 to 30. 9 . The composition according to claim 6 , wherein the filler has a ratio of D90 particle diameter to D50 particle diameter of 7 or less. 10 . The composition according to claim 6 , wherein the filler has a ratio of a D90 particle diameter to a D10 particle diameter of 50 or less. 11 . The composition according to claim 1 , wherein the amount of the phase change material is 10 to 60 parts by weight relative to 100 parts by weight of the silicone resin component. 12 . The composition according to claim 1 , wherein the amount of the filler is 60 to 200 parts by weight relative to 100 parts by weight of the silicone resin component. 13 . The composition according to claim 1 , wherein an amount of the filler is 50 parts by weight to 1,000 parts by weight relative to 100 parts by weight of the phase change material.

14. A method for preparing a composition according to any one of claims 1 to 13, comprising: mixing the phase change material with the silicone resin component and the filler, wherein the mixing is performed in a state wherein the phase change material is in a molten state.

15. A cured body of the composition according to any one of claims 1 to 13.

16. A battery module, comprising: a plurality of battery cells; as well as The composition according to any one of claims 1 to 13 or a cured product of the composition, The composition or the cured body covers at least a portion of the plurality of battery cells. The battery module according to claim 16 , wherein the battery cells are cylindrical battery cells.

Citation Information

Patent Citations

  • Non-aqueous solvent for removing acid gases from process gas streams in high pressure applications

    KR1020220108817A

  • Exterior panel combination and fixing structure for building

    KR1020230113206A